Beeinflussung der Eigenschaften von Sprühpolymerisationsprodukten. Issue 4 (17th March 2017) - Franke, Katharina; Moritz, Hans‐Ulrich; Pauer, Werner
Abstract: Spray polymerization combines shaping, drying, chemical reaction, and comminution in a single process step, thus saving process costs and time. Here, the application of a vibrating orifice spray head as a model atomization system is discussed with regard to the mass of atomizing air and the resulting particle size evolution determined. For the spray polymerization of partially neutralized acrylic acid, the influence of degree of neutralization, process temperature, and gas composition on particle morphology, residual moisture content, and residual monomer fraction are determined.